Palmatine attenuates LPS‐induced inflammatory response in mouse mammary epithelial cells through inhibiting ERK1/2, P38 and Akt/NF‐кB signalling pathways. Issue 1 (31st August 2020) - Ma, He; Zhang, Yufei; Wang, Jiaxin; Guo, Wenjin; Hu, Guiqiu; Xie, Shengnan; Yang, Zhanqing; Liu, Juxiong; Fu, Shoupeng
Abstract: Palmatine has a wide range of pharmacological effects and anti‐inflammatory function. However, the effect of palmatine on LPS‐induced inflammatory response of mammary epithelial cells has not been reported. In this research, we studied the anti‐inflammatory mechanism of palmatine in EpH4‐Ev (mouse mammary epithelial cells). EpH4‐Ev cells were pre‐treated with palmatine and then incubated with LPS. Cells were collected for examining production of pro‐inflammatory mediators by qRT‐PCR, and the related inflammatory signalling pathway was detected through immunofluorescence and Western blot. The results found that palmatine could significantly reduce the expression of IL‐6, TNF‐α, IL‐1β and COX‐2 in EpH4‐Ev cells. Research on mechanisms found that palmatine could significantly inhibit the protein levels of p‐Akt, p‐P65, p‐ERK1/2 and p‐P38 in EpH4‐Ev cells. In conclusion, these data suggested that palmatine inhibits inflammatory response in LPS‐induced EpH4‐Ev cells via down‐regulating Akt/ NF‐кB, ERK1/2 and P38 signalling pathways.